2007
DOI: 10.1161/01.hyp.0000259667.22309.df
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Shear Stress Determines Circulating Levels of Endothelial Microparticles in End-Stage Renal Disease

Abstract: Abstract-Shear stress is a major determinant of endothelial apoptosis, but its role in the in vivo release of shed membrane microparticles by endothelial cells remains unknown. Thus, we sought to evaluate the possible relationship between circulating endothelial microparticle levels and laminar shear stress in end-stage renal disease patients with high cardiovascular risk, whose levels of endothelial microparticles are elevated. In 34 hemodialyzed patients, we analyzed the relationships between brachial artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 41 publications
7
108
1
3
Order By: Relevance
“…In the present study, all patients with CKD-AP had chronic kidney vascular disease associated with CKD. Accordingly, our findings are supported by those of previous reports 42,43) . The circulating MP levels are strongly associated with acute coronary syndrome 31) and diabetes mellitus 33) , both of which are indicators of CAD and atherosclerosis.…”
Section: Conflicts Of Interestsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, all patients with CKD-AP had chronic kidney vascular disease associated with CKD. Accordingly, our findings are supported by those of previous reports 42,43) . The circulating MP levels are strongly associated with acute coronary syndrome 31) and diabetes mellitus 33) , both of which are indicators of CAD and atherosclerosis.…”
Section: Conflicts Of Interestsupporting
confidence: 94%
“…Furthermore, although the creatinine level ( Table 4) was found to be significantly correlated with high circulating levels of EDAp-MPs and PDAp-MPs, neither a reduced eGFR nor increased creatinine level (an indicator of CKD) were identified to be independently predictive of an increased circulating level of MPs. A previous study demonstrated that, even in patients with severe CKD (end-stage renal disease on hemodialysis), the circulating MP levels were significantly increased only in the presence of reduced whole blood viscosity and shearing stress 42) . Other authors have documented elevated levels of MPs due to acute vascular damage, rather than chronic vasculitis, resulting from renal disease 43) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Renal disease, [25][26][27] hypertension, 28 thrombotic thrombocytopenic purpura, 29 and pregnancy 30 promote the release of endothelial microparticles. A wide range of diseases and insults are also associated with the generation of platelet and leukocyte microparticles.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have shown that diseases of the vasculature and kidneys, including CKD, are associated with increased numbers of circulating endothelial microparticles 17, 18, 19, 20, 21, 22. We have previously reported that the microparticles released from endothelial cells can, under some conditions, activate the complement system, and that generation of complement‐activating microparticles is associated with vascular and renal injury in mice 23.…”
Section: Introductionmentioning
confidence: 98%